Aortic-Brachial Stiffness Mismatch and Mortality in Peritoneal Dialysis Patients - WenHan Bao; FangYu Wang; Wen Tang (Karger Publishers, 2019)
Background/Aims: Possible predictive value of aortic-brachial arterial stiffness mismatch assessed by pulse wave velocity PWV ratio in peritoneal dialysis patients' outcomes need to be further elucidated. The aim of this study is to investigate the predictor value of PWV ratio on peritoneal dialysis (PD) patients' outcomes in China. Methods: In this longitudinal cohort study, patients who started PD during September 20, 2005, to February 05, 2008, were included. All the patients were followed until January 31, 2018. Aortic-brachial arterial stiffness mismatch was assessed using carotid-femoral pulse wave velocity divided by carotid-radial pulse wave velocity (PWV ratio). Results: A total of 181 incident PD patients were included. The median survival of patients in PWV ratio above median group (4.03 years, 95% CI 4.64-7.99 years) was shorter than that of PWV ratio below median group (10.43 years, 95% CI 9.74-11.12 years, p< 0.001). The cardiovascular mortality rate in PWV ratio above median group were significantly higher than that of PWV below median group (log rank test, p< 0.001). Univariate Cox regression analysis showed that both PWV ratio (HR 2.42, 95% CI 1.80-3.25, p< 0.001) and CF-PWV (HR 1.27, 95% CI 1.16-1.38, p< 0.001) were associated with high patients' all-cause mortality. Multivariable Cox regression analysis showed that the PWV ratio was a strong and significantly predictor of cardiovascular mortality (HR 2.08 95% CI 1.16-3.71, p=0.014) after adjusting for coronary heart disease history (HR 2.39, 95% CI 1.20-4.76, p=0.013), diabetes mellitus history (HR 2.84, 95% CI 1.51-5.33, p=0.001). However, the CF-PWV was failed to be included as a significant predictor for both all-cause and CVD mortality in the multivariable Cox regression model. Conclusion: Aortic-brachial arterial stiffness mismatch as assessed by PWV ratio, a new arteries stiffness risk parameter, is a significant prognostic indicator of CVD mortality in PD patients. We demonstrated that the discriminative power of the PWV ratio for both all-cause and CVD mortality was better than that CF-PWV.